Hubungan Jumlah Jenis Obat terhadap Kejadian Drug Related Problems (DRPs) pada Pasien Bronkitis Pediatri Rawat Jalan Rumah Sakit X Palembang Tahun 2015 - Yopi Rikmasari; Noprizon Noprizon; Raymond Hutagaol (Jurnal Penelitian Sains, 2017)
Drug-related problems (DRPs) are actual or potential events or circumstances that interfere with op-timal patient outcomes. Analysis of DRPs in bronchitis is important because bronchitis is one of the most com-mon respiratory infections in the community and needs special attention in pediatric patients, especially doses and limitations of the dosage form, so that pediatric patients are often given drugs in the form of dosage prepa-rations (pulveres) Which consists of several kinds of drugs. Polypharmacy is a large number of drugs in a pre-scription (and or without prescription) for inappropriate clinical effects. To decide carefully in identifying poly-pharmacy and stated that using more than the amount of drug that should be a potential risk of DRPs is limited assessment when assessing DRPs in a clinical setting. This study aims to determine the relationship between the number of drugs with the incidence of DRPs in child bronchitis patients in RS X Palembang. This research is a retrospective observational study, using analytical quantitative research method with de-scriptive design in the form of correlation study. Sources of data were obtained from secondary data, ie medi-cal records and recipes, using obervation sheet research instruments. The population is outpatient pediatric patients with a diagnosis of bronchitis at Palembang Hospital "X" in 2015. This study was conducted on all pop-ulations meeting the inclusion criteria. The results showed that there was a correlation (R = 0.473) between the number of drugs with the incidence of Drug Related Problems (DRPs) in the medium category and there was a positive correlation between the two variables ie the increasing number of drugs will increase the incidence of Drug Related Problems (DRPs).